An experimental study the impact of the hydrogen enrichment on cycle-to-cycle variations of the large bore and lean burn natural gas spark-ignition engine. (15th December 2020) - Duan, Xiongbo; Deng, Banglin; Liu, Yiqun; Zou, Shunzhang; Liu, Jingping; Feng, Renhua
Highlights: The impact of hydrogen ratio on cycle-to-cycle variations of the natural gas SI engine was studied. CA50 combustion phase advanced and its cycle-to-cycle variations reduced with increasing hydrogen. Combustion duration shortened and its cycle-to-cycle variations decreased with increasing hydrogen. Abstract: In this study, in order to investigate the impacts of the hydrogen enrichment on the combustion cyclic variability, five cases with different hydrogen energy shares were selected to unveil their influences on the cycle-to-cycle variations of the large bore and lean burn natural gas SI engine. The results indicated that the cycle-to-cycle variations of the indicated mean effective pressure of the test engine decreased with increasing the hydrogen energy share. Moreover, the coefficient of variation of the peak combustion pressure (PCP) was 8.75% without the hydrogen addition, while the coefficient of variation of the PCP was only 2.82% with 27.68% hydrogen energy share. Additionally, the average start of combustion (SOC) was advanced, while the cycle-to-cycle variations of the SOC did not show obvious improvement with increasing the hydrogen ratio. In addition, the average CA50 combustion phase advanced, and its cycle-to-cycle variations reduced with increasing hydrogen energy ratio. The average combustion duration was shortened with increasing the hydrogen energy share. The cycle-to-cycle variations of the combustion duration reduced by 5.4% with adding 27.68% hydrogen energy share compared to the case of without hydrogen addition. Finally, no matter with hydrogen enrichment or not, the values of the correlation coefficients of the PCP and the CA50 combustion phase were all greater than 0.8, which meant the PCP and the CA50 combustion phase were strongly related.